2015
DOI: 10.1556/0806.43.2015.014
|View full text |Cite
|
Sign up to set email alerts
|

In silico cloning and chromosomal localization of EST sequences that are related to leaf senescence using nulli-tetrasomes in wheat

Abstract: Leaf senescence is a notably important trait that limits the yield and biomass accumulation of agronomic crops. Therefore, determining the chromosomal position of the expression sequence tags (ESTs) that are associated with leaf senescence is notably interesting in the manipulation of leaf senescence for crop improvement. A total of 32 ESTs that were previously identified during the delaying leaf senescence stage in the stay-green wheat cultivar CN17 were mapped to 42 chromosomes, a chloroplast, a mitochondrio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The source/sink relationship is a dynamic balance [ 5 ], and a better understanding of this relationship using different wheat genotypes would contribute to both the elucidation of yield formation mechanisms and systematic yield improvement. Some authors have suggested that wheat genotypes that differ in both the onset and the speed of leaf senescence are ideal for analyzing the source/sink relationship [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The source/sink relationship is a dynamic balance [ 5 ], and a better understanding of this relationship using different wheat genotypes would contribute to both the elucidation of yield formation mechanisms and systematic yield improvement. Some authors have suggested that wheat genotypes that differ in both the onset and the speed of leaf senescence are ideal for analyzing the source/sink relationship [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 10,746 ESTs or cDNA of Oryza sativaas on date 5.4.2021 that have been expressed under drought conditions were downloaded from the EST database of NCBI (www.ncbi.nlm.nih.gov). Later, redundant ESTs, low complexity sequence, vector sequence, genomic repeats were masked by EGassembler (Guo et al, 2015,Masoudi-Nejad et al, 2006. The CAP3 programme was used to aggregate the processed EST sequences into clusters (Huang & Madan 1999).…”
Section: Methodsmentioning
confidence: 99%
“…There were 6,717 ESTs of T. aestivum obtained from the EST database in NCBI (www.ncbi.nlm.nih.gov) containing all the entries from the GenBank database of the EST or cDNA categories that have been expressed in drought and saline conditions until now. The ESTs were masked to exclude sequence parts that could cause incorrect clustering [15] and then were masked for genomic repeats, vector sequence, low complexity sequence (including poly-A tails), and sequencing artifacts by EGassembler [22]. The processed EST sequences were grouped into clusters using the CAP3 program [23].…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing projects for ESTs have been performed for various organisms, creating millions of short, single-pass nucleotide-sequence reads, and are available from EST databases. Inclusive computational strategies have been advanced to regulate and analyze EST data for gene discovery, transcription, and functional annotation for products of a putative gene [15]. Similar studies on EST sequences have been performed on wheat for biotic stress and on Brassica rapa [16].…”
Section: Introductionmentioning
confidence: 99%